GIS to Explore the Geographical Mysteries of Oral Cancer: Geospatial Distribution of Patients Diagnosed with Oral Potentially Malignant Disorders at the University Dental Hospital Peradeniya - Athukorala, Isuru; Medawela, R.M.S.H.B; Gunawardana, Malika; Jayasinghe, R.D. (Asian Pacific Journal of Cancer Care, 2022)
Background: Oral cancers which are often preceded by an oral potentially malignant disorder (OPMD) carries the highest mortality rate among all cancers in Sri Lanka. Dental Teaching Hospital, Peradeniya is one of the tertiary centres in Sri Lanka for treating OPMD with a high patient turnover. Objectives: This study aimed to determine the geospatial distribution of OPMD patients who attended Dental Hospital, Peradeniya (DHP) using geocoding methods. Materials and Methods: A retrospective study was done by obtaining data of 869 OPMD patients who visited DHP within the last 4 years to geo-code their addresses using GIS software. Results: The majority of the sample consisted of oral lichen planus (OLP) (52.47%). 29% and 18.64% of the patients were diagnosed with leukoplakia and oral submucous fibrosis (OSF) respectively. Most of the OPMD patients (60.64%) who visited the clinic were from the Kandy district and surprisingly the majority of OPMD patients had been reported from non-estate areas. The second and third highest number of patients were respectively from Nuwaraeliya (11.28%) and Kegalle (7.48%). More than half (57.19%) of the patients were living within 20 km of the hospital. Conclusion: The composition of patients with OPMDs visited the DHP had deviated from the national data. More than half of the sample residing within a reasonable travel distance to a specialist care centre.